AVALIAÇÃO DO IMPACTO DE AÇÕES PARA PROMOÇÃO DO CONSUMO DE FRUTAS E HORTALIÇAS NO AMBIENTE DE TRABALHO - Amanda da Silva Franco (Universidade do Estado do Rio de Janeiro, 2014)
To assess the impact of actions to promote the consumption of fruits and vegetables (FV) in the workplace.Non-randomized before and after intervention study with historical control group, in a public companydirected to scientific research. The study population were employees who had lunch in the restaurant of thecompany in the days of the study. At the pre-intervention survey, data about both the company studied (A)and the one responsible for supplying meals (B), socio demographic characteristics and FV consumptionof subjects studied, and their opinions on topics related to FV were collected. It was also conducted a focusgroup with opinion makers of the company in order to identify the determinants of their FV consumptionaiming to subsidize the construction of strategies for FV promotion. The intervention lasted for eightmonths and was composed by two lines: environmental (restaurant) and education (directed to individuals).At the first one, activies were developed to sensitize the B"s manager and nutritionist about the importanceof promoting FV and regular contacts were made to subsidize her to offer FV in the restaurant. At thesecond one, presential activities were performed, materials were distributed and electronic communicationstrategies were developed. At the pos-intervention survey, besides FV consumption by employees, the levelof exposure to the intervention and their opinion about changes in the restaurant in terms of FV supplywere recorded. The analysis of the impact of the intervention consisted in the exam of the relevance ofthe difference between proportions or means obtained before and after the intervention. The associationbetween intervention and outcomes was examined by multiple regression models controlling for the initialFV intake and individuals socio demographic factors. We studied 61 individuals. The average coverage ofactivities and educational materials was 63.5%. Nearly 2/3 of employees noticed a change in at least twoaspects related to appearance and variety of preparations. At the second survey, 88.6% of the employeestrusted in the hygiene of raw FV comparing to 56.9% in the first survey. There was an increase of 53.6 g(38%) in the consumption of FV at lunch. The regular consumption of vegetables increased from 47.5 to72.1%, and the average number of days of consumption of vegetables increased from 4.4 to 5.6 days. It wasfound association between the increase in the consumption of FV and positive change in confidence in thehygiene of raw FV; increase in consumption of vegetables and both positive change in confidence in the hygiene of raw FV and level of exposure to the educational aspect of the intervention, and increase in theaverage days of consumption of vegetables and perceived positive changes in the variety and presentationof preparations with FV. There was an increase in consumption of FV among employees exposed to theintervention. Its multicomponent design seems to have contributed to the study's findings. DOI 10.12957/demetra.2014.10829